(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article explores the strategic development of multilingualism within Uzbekistan’s higher education system, emphasizing policy integration, pedagogical transformation, and digital innovation. With growing demands for global competitiveness and national identity preservation, Uzbekistan aims to modernize its tertiary education through multilingual programs involving Uzbek, Russian, and English. Drawing on national reforms and institutional case studies, the article identifies existing challenges—such as teacher preparedness and resource limitations—and proposes viable approaches, including curriculum redesign, ICT integration, and multilingual teacher training. The paper concludes with actionable recommendations for advancing an inclusive, functional multilingual higher education framework.